Impact of Intra‐ and Extra‐Osseous Soft Tissue Composition on Changes in Bone Mineral Density With Weight Loss and Regain - Bosy‐Westphal, Anja; Later, Wiebke; Schautz, Britta; Lagerpusch, Merit; Goele, Kristin; Heller, Martin; Glüer, Claus‐C.; Müller, Manfred J. (Obesity (Silver Spring, Md.), 2011)
Recent studies report a significant gain in bone mineral density (BMD) after diet‐induced weight loss. This might be explained by a measurement artefact. We therefore investigated the impact of intra‐ and extra‐osseous soft tissue composition on bone measurements by dual X‐ray absorptiometry (DXA) in a longitudinal study of diet‐induced weight loss and regain in 55 women and 17 men (19–46 years, BMI 28.2–46.8 kg/m2). Total and regional BMD were measured before and after 12.7 ± 2.2 week diet‐induced weight loss and 6 months after significant weight regain (≥30%). Hydration of fat free mass (FFM) was assessed by a 3‐compartment model. Skeletal muscle (SM) mass, extra‐osseous adipose tissue, and bone marrow were measured by whole body magnetic resonance imaging (MRI). Mean weight loss was −9.2 ± 4.4 kg (P < 0.001) and was followed by weight regain in a subgroup of 24 subjects (+6.3 ± 2.9 kg; P < 0.001). With weight loss, bone marrow and extra‐osseous adipose tissue decreased whereas BMD increased at the total body, lumbar spine, and the legs (women only) but decreased at the pelvis (men only, all P < 0.05). The decrease in BMDpelvis correlated with the loss in visceral adipose tissue (VAT) (P < 0.05). Increases in BMDlegs were reversed after weight regain and inversely correlated with BMDlegs decreases. No other associations between changes in BMD and intra‐ or extra‐osseous soft tissue composition were found. In conclusion, changes in extra‐osseous soft tissue composition had a minor contribution to changes in BMD with weight loss and decreases in bone marrow adipose tissue (BMAT) were not related to changes in BMD.